PERAN PLACE IDENTITY DALAM MENCIPTAKAN COMMUNITY RESILIANCE DI WILAYAH URBAN FRINGE - Ischak, Mohammad -; Setioko, Bambang -; Gandrum, Dedes Nur (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2018)
The urban growth in today's world is marked by rapid and massive urban expansion into rural areas. In the Tangerang area, the expansion is marked by the acquisition of agricultural land and settlements by developers as happened in the development of the new town of Gading Serpong. One of the impacts of land acquisition and settlement by developers has led to the emergence of many settlements confined within Gading Serpong's new town area. In spite of the changes in the immediate environment that are very fast and still going on today, changes also occur in native settlements, especially in the area because many land and its inhabitants are moved as a result of being freed by the developer. With very extreme changes occurring in the enclave settlement, raises the question of why and in what ways can an enclave settlement survive?To get answers to these questions, it is necessary to study the characteristics of settlements and indigenous peoples, as well as to examine the potential of the region in the context of place identity that can be maximized for the benefit of adaptation to environmental changes due to the growth of the region that is going on around it. The research use a qualitative method by obtaining the data directly through observation and in-depth interviews with residential dwellers to obtain the characteristics of settlements as well as characteristics of sosial life in the locus of study. The results obtained are that there is potential possessed by the native settlement that is place identity as the basis on the resilience of the inhabitants. Place identity is formed because of several factors that are actually very possible to synergize with all the factors involved in the growth of urban fringe. Thus it is expected that development in the urban fringe area will not leave the settlements and life of its pre-existing inhabitants as the content attached to the concept of sustainable development.Keywords : place identiry, sustainable development, segregasi, kebertahanan